1987
DOI: 10.1144/gsl.sp.1987.028.01.19
|View full text |Cite
|
Sign up to set email alerts
|

Crustal extension along a rooted system of imbricate low-angle faults: Colorado River extensional corridor, California and Arizona

Abstract: Summary The upper 10 to 15 km of crystalline crust in the 100-km-wide Colorado River extensional corridor of mid-Tertiary age underwent extension along an imbricate system of gently dipping normal faults. Detachment faults cut gently down-section eastward in the direction of tectonic transport from a headwall breakaway, best expressed in the Old Woman Mountains, California. Successively higher and more distal allochthons are displaced farther from the headwall, some as much as tens of kilometres. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 32 publications
3
150
0
Order By: Relevance
“…Davis and others (1986) applied the Wernicke model to a middle Tertiary detachment fault in southeastern California and another in southeastern Arizona and showed that slip on ductile, semiductile, and brittle components of the nowundulating detachment systems was all in the same downdip sense, in terms of the model. Howard and John (1987) applied the model to detachment faults exposed in the lower Colorado River region, where the structures cut deeply into middle-crust rocks and where the indicated master faults dip toward and beneath the Colorado Plateau, not away from it as in the southern Great Basin. Howard and John demonstrated that the detachment faults obliquely truncated thick crustal sections, in both upper and lower plates, in the sense required by the model; they also showed that major anastomosing or imbricate faults had originated in the middle crust, not just a single master fault.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davis and others (1986) applied the Wernicke model to a middle Tertiary detachment fault in southeastern California and another in southeastern Arizona and showed that slip on ductile, semiductile, and brittle components of the nowundulating detachment systems was all in the same downdip sense, in terms of the model. Howard and John (1987) applied the model to detachment faults exposed in the lower Colorado River region, where the structures cut deeply into middle-crust rocks and where the indicated master faults dip toward and beneath the Colorado Plateau, not away from it as in the southern Great Basin. Howard and John demonstrated that the detachment faults obliquely truncated thick crustal sections, in both upper and lower plates, in the sense required by the model; they also showed that major anastomosing or imbricate faults had originated in the middle crust, not just a single master fault.…”
Section: Discussionmentioning
confidence: 99%
“…The many gently dipping normal faults within Bare Mountain, for example, indicate much extension there. Major ductile or semiductile faults within the lower plates have not yet been proved within the Death Valley region but have been identified beneath ductile detachment faults elsewhere in the Basin and Range province (Hamilton, 1987;Howard and John, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The detachment fault divides the bedrock geology of the area into two parts: an extended upper plate of Proterozoic, Paleozoic, Mesozoic, and Tertiary metamorphic, igneous, and sedimentary rocks, and a lower plate of Tertiary plutons and mylonite and mylonitic gneiss that were derived from Proterozoic, Paleozoic, Mesozoic, and Tertiary metamorphic, igneous, and sedimentary protoliths. Mylonitic deformation in the lower plate is considered to be a deeper level expression of, and slightly older than, brittle extensional faulting along the detachment fault and its upper plate (Davis, 1983;Spencer and Reynolds, 1986a;Howard and John, 1987;Davis and Lister, 1988). Syntectonic sedimentation and volcanism accompanied extension, and these rocks now crop out in the highly faulted upper-plate terrane (Davis and others, 1980;Otton, 1982;Spencer and.Reynolds, 1986b).…”
Section: Character and Settingmentioning
confidence: 99%
“…2). Mylonitic deformation in the lower plate is considered to be a deeper level expression of, and slightly older than, brittle extensional ,faulting along the detachment fault and its upper plate (Davis, 1983;Spencer and Reynolds, 1986a;Howard and John, 1987;Davis and lLister, 1988). Syntectonic sedimentation and volcanism accompanied extension, and these rocks now crop out in the highly faulted upper-plate terrane (Davis and oth~rs, 1980;Spencer and Reynolds, 1986b).…”
Section: U S Geological Surveymentioning
confidence: 99%
“…Movement of the upper plate was northeastward (Shackelford, 1980). The study area is in the 60-mi-wide Colorado River extensional corridor, across which slip on all faults is estimated to total about 30 mi (Howard and John, 1987). Age of inception of the extensional movement is not known.…”
Section: Geologymentioning
confidence: 99%